Nexus among agricultural extension services, women’s empowerment in agriculture, and farm income in Bangladesh - Begum, Ismat Ara; Alam, Mohammad Jahangir; Sarma, Paresh Kumar; Cooper, Bethany; Crase, Lin; Sayem, Sheikh Mohammad (Bangladesh Agricultural University, 2023)
The economic inclusion of women in the agricultural sector plays a crucial role in boosting productivity, increasing food security, and improving rural livelihoods in developing countries. However, women’s empowerment FROM RESEARCH TO IMPACT, October 2023 39 within this sector faces persistent social obstacles and economic constraints. Agricultural extension service programs provide farmers with education and support to increase agricultural productivity. However, such programs tend to favor the development of male farmers, perpetuating the exclusion of women. This study examines the nexus between agricultural extension services, women’s empowerment, and rice farm income. Data from the Bangladesh Integrated Household Survey of 2015 and 2018 were used. We find that participation in agricultural extension services resulted in a 16.36% increase in the Women’s Empowerment in Agriculture Index over three years, rising from 0.605 in 2015 to 0.704 to 2018. Rice farmers who participated in agricultural extension services received, on average, 31.61% more income than those in the nonparticipant group. Furthermore, those who participated in agricultural extension services increased their income by 2.63% between 2015 and 2018, indicating a cumulative positive effect over time. This study establishes a significant nexus among agricultural extension services, women’s empowerment, and farm income in Bangladesh. The government must formulate policies to deliver agricultural extension services through the timely recruitment and periodic training of delivery agents, as well as the provision of adequate logistics.